1984
DOI: 10.1159/000118144
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis, Atropine, and Temporal Information Processing

Abstract: In experiment 1, subjects judged time by duration production under no-counting instructions. The productions were made following intravenous injection of atropine sulfate or saline, and after smoking cigarettes with and without (–)-Δ9-tetrahydrocannabinol (THC). THC increased the subjective time rate (STR); i.e., the rate at which subjective time passes relative to clock time, whereas atropine had no effect on STR. Thus, reduction in central acetylcholine activity is not a sufficient explanation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…In addition to its role in motor coordination, the cerebellum is thought to play a key role in temporal operations such as rhythm production, time estimation, and some forms of associative learning (Ivry and Keele, 1989;Katz and Steinmetz, 2002;Leiner et al, 1991). Indeed, altered time perception is one of the most frequently reported subjective experiences associated with acute cannabis intoxication (Hicks et al, 1984;Mathew et al, 1998), which is thought to be modulated by the cerebellum (O'Leary et al, 2003). Thus, studies examining cerebellar-mediated processes may provide important clues in relation to the subjective effects of cannabis and the role of the endocannabinoid system in normal brain function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its role in motor coordination, the cerebellum is thought to play a key role in temporal operations such as rhythm production, time estimation, and some forms of associative learning (Ivry and Keele, 1989;Katz and Steinmetz, 2002;Leiner et al, 1991). Indeed, altered time perception is one of the most frequently reported subjective experiences associated with acute cannabis intoxication (Hicks et al, 1984;Mathew et al, 1998), which is thought to be modulated by the cerebellum (O'Leary et al, 2003). Thus, studies examining cerebellar-mediated processes may provide important clues in relation to the subjective effects of cannabis and the role of the endocannabinoid system in normal brain function.…”
Section: Introductionmentioning
confidence: 99%
“…Of the experiments which have evaluated cannabinoid effects on time estimation, several have shown that direct cannabis administration induces temporal disintegration, which is typically exhibited in the form of increased internal clock speeds (the experience of time passing more slowly; Hicks et al, 1984;Mathew et al, 1998;O'Leary et al, 2003). In relation to cerebellar modulation of cannabis' effect on time perception, a study integrating behavioral measures of temporal processing with neuroimaging methodologies has yielded positive results.…”
Section: Introductionmentioning
confidence: 99%
“…Although subjects report that cannabis makes time pass very slowly (Moreau de Tours, 1845; Tart, 1970), the majority of clinical studies on the subject reveal that cannabinoids increase the rate at which subjective time passes relative to clock time (Atakan et al, 2012;Hicks et al, 1984;O'Leary et al, 2003). This cannabinoid-induced acceleration of an internal clock likely contributes to subjects increasing self-timed behaviors, such as counting and tapping, and overestimating periods of elapsed time ( .…”
Section: Discussionmentioning
confidence: 99%
“…Time is said to slow down: 'the minutes become hours, the hours become days; soon any precise idea of duration escapes us' (Moreau de Tours, 1845). Experimental studies suggest that cannabinoids slow down time by speeding up an internal clock (Hicks et al, 1984;Tinklenberg et al, 1976), so that an accelerated internal pace gives rise to the subjective impression that time is slowing (Atakan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…bital (Goldstone & Kirkham, 1968), ethanol (Tinklenberg, Roth, & Koppell, 1976), and cyclopropane (Adam, Rosner, Hosick, & Clark, 1971) are associated with reductions in verbal estimates of duration, whereas stimulants such as amphetamines (Church, 1984;Goldstone & Kirkham, 1968) and marijuana (Hicks, Gualtieri, Mayo, & Perez-Reyes, 1984;Tinklenberg et al, 1976) are associated with increased verbal estimates ofduration, implying that the internal clock is running too fast. On the cognitive side, there is good evidence that more demanding or more complex tasks are associated with shorter verbal estimates ofduration in the prospective paradigm, in which subjects know in advance that they will be asked to estimate the time interval Hicks et al, 1976).…”
mentioning
confidence: 99%